Restless Legacies : Contemporary Craft Practice in Canada. - Weir, Jean B.; Falk, Lorne; Doyon, Carol; Petro-Canada Centre, Calgary; Olympic Arts Festival Calgary 1988 (Calgary : Olympic Arts Festival, 1988)
Anderson, Jackie ; Caldwell, Dorothy ; Chalke, John ; Dexter, Walter ; di Petta, Angelo ; Haufschild, Lutz ; Heinemann, Steve ; Heisler, Franklyn ; Held, Robert ; Rooke, Fay ; Sabiston, Carole ; Saito, Satoshi ; Saito, Louise Doucet ; Schantz, Karl ; etc.
Restless Legacies : Contemporary Craft Practice in Canada / Traditions en évolution : L'artisanat contemporain au Canada, Petro-Canada Centre, Calgary, January 29 to February 26, 1988
boek